E-cigarette addiction and harm perception: Does initiation flavor choice matter? - Man Hung; Andrew Spencer; Eric S. Hon; Frank W. Licari; Val Joseph Cheever; Ryan Moffat; Clarissa Goh; Ben Raymond; Martin S. Lipsky (BMC, 2022)
Abstract Introduction The 21st century was marked by a dramatic increase in adolescent e-cigarette use in the United States (US). The popularity of non-traditional flavor types, including fruit and pastry, is thought to contribute toward growing product use nationally, leading to a variety of federal and state regulations limiting the use of non-traditional flavors in the US. The relationship between flavor type and increased adolescent use suggests a possible link between flavor use and addiction and harm perception. This study assessed if the flavor type used when initiating e-cigarette use predicted addiction and harm perceptions. Methods The study utilized data from the multi-wave youth Population Assessment of Tobacco Health Study. It explored the impact initiating e-cigarette use with traditional versus non-traditional flavor types among cigarette users on the outcome variables: e-cigarette addiction and harm perception. Both e-cigarette addiction and harm perception were measured using self-report, Likert scale questionnaires. Descriptive statistics characterized the study variables and linear regression analyses performed to test whether flavor initiation type is associated with addiction and harm perception. Results The study sample consisted of 1,043 youth (weighted N = 1,873,617) aged 12 to 17 years who reported at least one instance of e-cigarette use. After adjusting for age, age of onset, sex, race and annual household income there was no statistically significant difference in addiction levels between those initiating with traditional versus non-traditional flavors (p = 0.294). Similarly, traditional versus non-traditional flavor initiation did not show a statistically significant difference in adolescent e-cigarette harm perceptions (p = 0.601). Conclusions Traditionally flavored e-cigarette initiation produces similar risk for addiction and harm perceptions as non-traditionally flavored initiation. These findings suggest that banning non-traditional flavors alone may be ineffective in curbing e-cigarette addiction and harm perception. Additional research is needed to better understand which e-cigarette product characteristics and behaviors may be associated with greater addiction and reduced harm perceptions.